Proceedings. The 21st Digital Avionics Systems Conference
DOI: 10.1109/dasc.2002.1052981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of primary flight symbology on workload and situation awareness in a head-up synthetic vision display

Abstract: Precision navigation, display, and avionics technologies have progressed to the point that a head-up primary flight display incorporating synthetic elements such as terrain and commanded flight path is a possibility in the near future. The goal of such a display is to increase situation awareness and reduce aircrew reliance on warning systems or automation to prevent controlled flight into terrain (CFIT) mishaps. The primary flight display-and primary focus of attention-in modern fighter aircraft is a head-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Tole et al (1982) suggest that the conceptual transformation of digital data to an analog representation will result in longer visual fixations and processing time and may increase the probability of error. The detrimental effects of increased duration of visual fixations have been demonstrated by Williams (2002) and Snow and French (2002) while assessing the highway-in-the-sky (HITS) instrument display. These studies showed that pilots increased their gaze time towards the HITS instrument display at the cost of monitoring other instruments and their immediate surroundings, thus reducing situational awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Tole et al (1982) suggest that the conceptual transformation of digital data to an analog representation will result in longer visual fixations and processing time and may increase the probability of error. The detrimental effects of increased duration of visual fixations have been demonstrated by Williams (2002) and Snow and French (2002) while assessing the highway-in-the-sky (HITS) instrument display. These studies showed that pilots increased their gaze time towards the HITS instrument display at the cost of monitoring other instruments and their immediate surroundings, thus reducing situational awareness.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, significant decreases in pilot workload while using perspective displays were reported. These improvements to SA and workload were associated with significant improvements in flight technical error [5]. Such improvements result fkom the similarities between the synthetic image and the real-world image that the pilot would have if there were no restrictions to visibility.…”
Section: Introductionmentioning
confidence: 80%
“…The presence of EV and SV imagery for the pilot flying (PF) has not been found to have a significant influence on flight path tracking performance when compared to the overwhelming influence of flight guidance symbology Snow & French, 2002) unless, however, the guidance information is cluttered by SV or EV imagery (Schnell, Theunissen, & Rademaker, 2005).…”
Section: Ev and Sv Designs For Pilot Flyingmentioning
confidence: 98%